2019
DOI: 10.1093/biolre/ioz230
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Fbxw7 in Sertoli cells impairs testis development and causes infertility in mice†

Abstract: F-box and WD-40 domain protein 7 (Fbxw7) is a component of the Skp1-Cdc53/Cullin-F-box-protein complex (SCF/β-TrCP), which is an E3 ubiquitin ligase that mediates protein degradation. This complex has recently been shown to negatively regulate spermatogonial stem cell self-renewal; however, its roles in Sertoli cell (SC) proliferation, differentiation, and function remain to be established. In this study, we generated conditional mutant mice with SC-specific deletion of Fbxw7 via the Cre-loxP system. Fbxw7 def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These isoforms exhibit distinct subcellular localizations: FBXW7 α in the nucleus, FBXW7 β in the cytoplasm, and FBXW7 γ in the nucleolus. 20 Our findings indicate that FBXW7 primarily exists as α and β isoforms in oocytes. Research has demonstrated that deletion of FBXW7 in tumour cells leads to mitotic defects and chromosomal instability, promoting tumorigenesis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…These isoforms exhibit distinct subcellular localizations: FBXW7 α in the nucleus, FBXW7 β in the cytoplasm, and FBXW7 γ in the nucleolus. 20 Our findings indicate that FBXW7 primarily exists as α and β isoforms in oocytes. Research has demonstrated that deletion of FBXW7 in tumour cells leads to mitotic defects and chromosomal instability, promoting tumorigenesis.…”
Section: Discussionmentioning
confidence: 64%
“… 37 Our previous work established the role of FBXW7 in Sertoli cell differentiation in male gonads, with its absence disturbs Sertoli cell differentiation and thus disrupts testicular development. 20 Similarly, in the nematode Caenorhabditis elegans, the FBXW7 homologue SEL‐10 coordinates meiosis and post‐transcriptional gene expression during gametogenesis through the MPK‐1/MAPK pathway. 38 Moreover, during primordial follicle development, FBXW7 inhibits primordial follicle activation via the eNOS/cGMP/PKG pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Moreover, FBXW7 (also known as FBXO30), a component of the SCF E3 ligase, is also indispensable for mouse spermatogenesis via the regulation of spermatogonial stem cell self-renewal 40 and the maintenance of Sertoli cell maturation and function. 41 Thus, it seems reasonable to postulate that FBXO43 might modulate mammalian spermatogenesis as a core subunit of the SCF complex. The SCF E3 ligase consists of four major components: Cullin1 (CUL1), RING box subunits (RBX1), SKP1, and an F-box protein.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the anti-CREST antibody (Proteintech, 12439-1-AP; immunogen: C-terminal amino acids 47-396 of human CREST) utilized in the present research has been tested on the human and mouse tissues by co-immunoprecipitation and immunohistochemistry analyses (Chesi et al 2013). The specificity of anti-WT1 antibody (Abcam, ab89901), anti-GATA-4 antibody (Abclonal, A3600), anti-Brg1 antibody (Santa Cruz, sc-17796) and anti-p300 antibody (Santa Cruz, sc-48343) has been tested on mouse tissues by immunofluorescence analysis (anti-WT1, anti-GATA-4 and anti-Brg1 antibodies) (Del Monte-Nieto et al 2018;Morohoshi et al 2019;Zhang et al 2019) and Western blot analysis (anti-WT1, anti-GATA-4, anti-Brg1 and anti-p300 antibodies) (Bao et al 2018;Dou et al 2018;Shorstova et al 2019;Zhang et al 2019). In addition, the specificity of the anti-CREST antibody was tested in the present study by Western blotting (Fig.…”
Section: Specificity Of the Primary Antibodiesmentioning
confidence: 99%